Spontaneous and induced ferroelectricity in the BiFe1−xScxO3 perovskite ceramics - Shvartsman, Vladimir V. (2021)
High-pressure synthesis method allows obtaining single-phase perovskite BiFe1-xScxO3 ceramics in the entire concentration range. As-prepared compositions with x from 0.30 to 0.55 have the antipolar orthorhombic Pnma structure but can be irreversible converted into the polar rhombohedral R3c or the polar orthorhombic Ima2 phase via annealing at ambient pressure. Microstructure defects and large conductivity of the high-pressure-synthesized ceramics make it difficult to study and even verify their ferroelectric properties. These obstacles can be overcome using piezoresponse force microscopy (PFM) addressing ferroelectric behavior inside single grains. Herein, the PFM study of the BiFe1-xScxO3 ceramics (0.30 ≤ x ≤ 0.50) is reported. The annealed samples show a strong PFM contrast. Switching of domain polarity by an electric field confirms the ferroelectric nature of these samples. The as-prepared BiFe0.5Sc0.5O3 ceramics demonstrate no piezoresponse in accordance with the antipolar character of the Pnma phase. However, application of a strong enough electric field induces irreversible transition to the ferroelectric state. The as-prepared BiFe0.7Sc0.3O3 ceramics show coexistence of ferroelectric and antiferroelectric grains without poling. It is assumed that mechanical stress caused by the sample polishing can be also a driving force of phase transformation in these materials alongside temperature and external electric field.